Male Perspective on Construction of Masculinity: Issues and Challenges in Lahore (Journal of Social Sciences Review, 2023)
Masculinity is the dominant gender discourse of masculine behaviour embedded in men’s everyday practices, behaviours, and actions. Since at least the 1980s, these gendered social norms have been argued to create stress, strain, and conflicts for men. Investigating those experiences and circumstances where gender patterns are less or more open to change is an important task of this research. Therefore, this study aims to include men in the “study up” approach of the gender research domain and include their experiences in the conversation of gendered lobbying under patriarchal perceptions. Using the Gender Role Strain paradigm as a guiding framework, the study intends to explore the male perspective on the construction of masculinity in contemporary Pakistani society. A qualitative phenomenological research design has been used, and snowball and purposive sampling techniques are used in conjunction for the recruitment of participants with the help of pre-defined inclusion criteria. The participants of the study are diverse in terms of age, educational background, and family situation. Each participant was interviewed at length using an in-depth interview guide, including topics from the beginning of childhood across the lifespan. The result of the interviews supports the social constructionist perspective of masculinity and also focuses on the strain and challenges of the masculine norms associated with the existing conceptions of masculinity and gender role strain.
Keywords: Male Perspectives; Masculinity; Gender Role Strain; Essentialism; Constructionism